Mapping of DNA methylation-sensitive cellular processes in gingival and periodontal ligament fibroblasts in the context of periodontal tissue homeostasis - Lagosz-Cwik, Katarzyna B.; Melnykova, Mariia; Nieboga, Elwira; Schuster, Aureliusz; Bysiek, Agnieszka; Dudek, Slawomir; Lipska, Weronika; Kantorowicz, Malgorzata; Tyrakowski, Michal; Darczuk, Dagmara; Kaczmarzyk, Tomasz; Gilijamse, Marjolijn; et al. (Frontiers in Immunology, 2023)
Interactions between gingival fibroblasts (GFs) and oral pathogens contribute to the chronicity of inflammation in periodontitis. Epigenetic changes in DNA methylation are involved in periodontitis pathogenesis, and recent studies indicate that DNA methyltransferase (DNMT) inhibitors may protect against epithelial barrier disruption and bone resorption. To assess the impact of DNMT inhibition on GFs, cells were cultured with decitabine (5-aza-2’-deoxycytidine, DAC) for 12 days to induce DNA hypomethylation. We observed several potentially detrimental effects of DAC on GF biological functions. First, extended treatment with DAC reduced GF proliferation and induced necrotic cell death. Second, DAC amplified Porphyromonas gingivalis- and cytokine-induced expression and secretion of the chemokine CCL20 and several matrix metalloproteinases (MMPs), including MMP1, MMP9, and MMP13. Similar pro-inflammatory effects of DAC were observed in periodontal ligament fibroblasts. Third, DAC upregulated intercellular adhesion molecule-1 (ICAM-1), which was associated with increased P. gingivalis adherence to GFs and may contribute to bacterial dissemination. Finally, analysis of DAC-induced genes identified by RNA sequencing revealed increased expression of CCL20, CCL5, CCL8, CCL13, TNF, IL1A, IL18, IL33, and CSF3, and showed that the most affected processes were related to immune and inflammatory responses. In contrast, the genes downregulated by DAC were associated with extracellular matrix and collagen fibril organization. Our observations demonstrate that studies of DNMT inhibitors provide important insights into the role of DNA methylation in cells involved in periodontitis pathogenesis. However, the therapeutic potential of hypomethylating agents in periodontal disease may be limited due to their cytotoxic effects on fibroblast populations and stimulation of pro-inflammatory pathways.